Fortællerens fødsel ud af snestormen: Om Johannes V. Jensens himmerlandshistorie »Kirstens sidste Rejse« - Ehlers Dam, Anders (Danske Studier, 2020)
In this article I analyze ‘Kirstens sidste Rejse’ [Kirsten’s Last Journey], one of Johannes V. Jensen’s stories from Himmerland, drawing on both the original version of the text published in 1901, and the version included in 1904 in Nye Himmerlandshistorier [New Stories from Himmerland]. At first sight, the story is realistic account of two men transporting a coffin with the corpse of an old woman from Aalborg to her home village in Himmerland where she is to be buried, and the violent snowstorm in which they are caught on the way. By the time they finally reach their destination, Christen Sørensen, who has been driving the horse-drawn carriage, has undergone a profound change. Earlier a silent person, he now recounts endlessly, with the same mechanical voice, the journey with the dead woman. In this article, I offer a reading of the story from the perspective of Maurice Blanchot’s literary theory, arguing that Johannes V. Jensen’s text can be read as an allegory of the becoming of the literary narration and its relation to the experience of death and nothingness.